2006
DOI: 10.1098/rspb.2006.3502
|View full text |Cite
|
Sign up to set email alerts
|

Copepods induce paralytic shellfish toxin production in marine dinoflagellates

Abstract: Among the thousands of unicellular phytoplankton species described in the sea, some frequently occurring and bloom-forming marine dinoflagellates are known to produce the potent neurotoxins causing paralytic shellfish poisoning. The natural function of these toxins is not clear, although they have been hypothesized to act as a chemical defence towards grazers. Here, we show that waterborne cues from the copepod Acartia tonsa induce paralytic shellfish toxin (PST) production in the harmful algal bloom-forming d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
215
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(233 citation statements)
references
References 48 publications
15
215
2
1
Order By: Relevance
“…(Selander et al, 2006), but the full induction takes 2-4 days (Selander et al, 2012), and is low with the low concentration of copepods used here (1 per 800 ml). Thus, it is assumed that the chemical profile of cells from the culture is representative for the experiments.…”
Section: Copepod Feeding Behaviormentioning
confidence: 88%
See 1 more Smart Citation
“…(Selander et al, 2006), but the full induction takes 2-4 days (Selander et al, 2012), and is low with the low concentration of copepods used here (1 per 800 ml). Thus, it is assumed that the chemical profile of cells from the culture is representative for the experiments.…”
Section: Copepod Feeding Behaviormentioning
confidence: 88%
“…Most previous studies of the response of copepods to toxic algae are incubation studies, in which the net outcome of the copepod-prey interaction is quantified in terms of feeding rate, prey selection, growth or egg production rate, or other similar bulk measures (reviewed by Turner, 2014). The direct video observation of individual responses and of direct copepod-prey cell interactions provided by this and a few other studies (Bruno et al, 2012;Hong et al, 2012;Tiselius et al, 2013) Selander et al, 2006;Teegarden, 1999). The fact that the copepods can distinguish between cells of very similar size and shape suggests that selection is mediated by chemical information.…”
Section: Repertoire Of Copepod Feeding Behaviors and Implications To mentioning
confidence: 95%
“…The cellular toxin quota appears to increase upon phosphorus limitation and decrease upon nitrogen limitation (van de Waal et al, 2014). One factor that has been found to lead to a several fold increase in cellular toxin quota is the presence of copepods and their waterborne cues (Selander et al, 2006;Wohlrab et al, 2010;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…the defense mechanism is inducible. Selander et al (2006) found that waterborne cues from the copepod Acartia tonsa induced paralytic shellfish poisoning toxin (PST) production in the dinoflagellate Alexandrium minutum, which led to reduced grazing of A. tonsa on A. minutum. It has also been shown that the chemical and morphological responses may take place simultaneously .…”
Section: Introductionmentioning
confidence: 99%